1972
DOI: 10.1136/adc.47.251.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diazepam Administered to Mothers During Labour on Temperature Regulation of Neonate

Abstract: . Effect of diazepam administered to mothers during labour on temperature regulation of neonate. Falls in temperature in the first nine hours after delivery were studied in a group of 12 babies whose mothers had received diazepam in labour, and in 13 comparable babies not exposed to diazepam. A significantly lower mean temperature was found in the test group within the first three hours. Cord blood levels of diazepam did not correlate with either maternal levels at delivery, the extent of the temperature drop,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Our finding of higher plasma diazepam levels in the babies than in the mothers agrees with those of others (Cavanagh and Condo, 1964;de Silva et al, 1964;Owen et al, 1972;Cree et al, 1973). The high level found in the baby born 15 minutes after drug administration to the mother shows that diazepam rapidly crosses the placenta.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding of higher plasma diazepam levels in the babies than in the mothers agrees with those of others (Cavanagh and Condo, 1964;de Silva et al, 1964;Owen et al, 1972;Cree et al, 1973). The high level found in the baby born 15 minutes after drug administration to the mother shows that diazepam rapidly crosses the placenta.…”
Section: Discussionsupporting
confidence: 93%
“…reported that diazepam given in doses greater than 30 mg to mothers in labour was associated with low Apgar scores, apnoea, reluctance to feed and impaired thermogenesis in the infant. Owen et al(1972) have also reported that body temperature tended to fall in babies born to mothers who had been given large doses of diazepam, but Lecart and Cavanagh (1964) found that large doses of diazepam given to the mother had no ill effects on the babies while McCarthy et a1 (1973) described two instances in which babies were severely asphyxiated at birth following the administration to the mother of large doses of diazepam amongst several other drugs. At delivery, the babies had higher plasma diazepam levels than the mothers and the diazepam levels in the babies rose over the next 48 hours.…”
mentioning
confidence: 99%
“…In most cases they indicate a slower disposition of the drug äs compared to children. No data on the metabolic disposition of benzodiazepines in the newborn infant have been available up to now, despite the fact that this class of drug is widely administered during gestation and labor [3,15], and in the first days of extrauterine life to control seizures [20]. In the present report we will describe some observations we were able to make on premature infants, full-term infants and children who received diazepam for therapeutic reasons.…”
mentioning
confidence: 79%
“…Obstetric reports indicate successful control of blood pressure and prevention of convulsions, with little evidence of harm to the newborn (Leinzinger 1969(Leinzinger , 1970Joyce and Kenyon, 1972). There have, however, been reports of hypotonia (Flowers et al, 1969;Rosanelli, 1970;Shannon et al, 1972), low Apgar scores (Flowers et al, 1969), and hypothermia (Owen et al, 1972). Hyperbilirubinaemia was found to be due to the vehicle, sodium benzoate, with which the parenteral preparation was prepared (Schiff et al, 1971).…”
Section: Introductionmentioning
confidence: 99%